Two if by sea : a novel - Mitchard, Jacquelyn (Simon & Schuster, 2016)
"Just hours after his wife and her entire family perish in the Christmas Eve tsunami in Brisbane, American expat and former police officer Frank Mercy goes out to join his volunteer rescue unit and pulls a little boy from a submerged car, saving the child's life with only seconds to spare. In that moment, Frank's own life is transformed. Not quite knowing why, Frank sidesteps the law, when, instead of turning Ian over to the Red Cross, he takes the boy home to the Midwestern farm where he grew up. Not long into their journey, Frank begins to believe that Ian has an extraordinary, impossible telepathic gift; but his only wish is to protect the deeply frightened child. As Frank struggles to start over, training horses as his father and grandfather did before him, he meets Claudia, a champion equestrian and someone with whom he can share his life and his fears for Ian. Both of them know that it will be impossible to keep Ian's gift a secret forever. Already, ominous coincidences have put Frank's police instincts on high alert, as strangers trespass the quiet life at the family farm"--Goodreads.com.